Predictors of partnership and sexual satisfaction and dyadic effects in couples affected by endometriosis and infertility - Eickels, Deborah van; Schick, Maren; Germeyer, Ariane; Rösner, Sabine; Strowitzki, Thomas; Wischmann, Tewes; Ditzen, Beate (Archives of gynecology and obstetrics, 2024)
PURPOSE: Endometriosis and infertility are associated with impaired partnership and sexuality of the patients, but also of their male partners. Also, endometriosis is one of the most common causes of infertility, resulting in a large overlap of both pathologies. The aim of this study was to determine the association of different predictors of partnership and sexual satisfaction and dyadic effects in couples with endometriosis and infertility. - METHODS: A cross-sectional study was conducted with n = 62 women with endometriosis and n = 46 partners, including a total of n = 44 couples, some of whom were affected by infertility. The questionnaire included items on partnership, sexuality, depression, social support, and desire for a child. Multiple linear regression and the actor-partner-interdependence-model were used for analysis. - RESULTS: Significant dyadic effects only occurred in couples with both endometriosis and infertility. Depression showed a significant negative actor effect in men for partnership satisfaction and a negative actor and partner effect in women for sexuality satisfaction (p < .05). For women, social support showed a significant positive actor effect for partnership satisfaction (p < .05), age showed a significant actor and partner effect for sexuality satisfaction (p < .05). - CONCLUSION: The results show a significant association of endometriosis and infertility with partnership and sexuality satisfaction. Infertility could be a decisive factor. However, the large overlapping of both endometriosis und infertility in many couples support the importance of further studies to differentiate between the both effects. - TRIAL REGISTRATION: German Clinical Trials Register DRKS00014362 on the 29.03.2018.